Quick Detection of FKS1 Mutations Responsible for Clinical Echinocandin Resistance in Candida albicans - Dudiuk, Catiana Beatriz (2015)
A rapid molecular-based assay for the detection of the Candida albicans FKS1 gene mutations responsible for resistance to echinocandin drugs was designed and evaluated. The assay consisted of a multiplexed PCR set of 5 tubes able to detect the most commonly described resistance mechanism, including FKS1 hot spot 1 and hot spot 2 mutations. The performance and specificity of the assay was evaluated using a double-blinded panel of 50 C. albicans strains. The assay showed a sensitivity of 96% and was able to detect all homozygous mutants included in the collection of strains, demonstrating that it is a robust, quick, and labor-saving method that is suitable for a routine clinical diagnostic laboratory.